PATOLOGI BIROKRASI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN SEMARANG - Dwi Nur Purwandri; Rina Martini (Journal of Politic and Government Studies, 2013)
In Semarang District Regional Employment Board to be a very important government agency. This is because one of the tasks is organizing pokonya monitoring, evaluation, and reporting on the implementation of the tasks field of personnel, training and education that includes planning and employee development, education and training, and mutation. With this task BKD to